2019
DOI: 10.3390/ijms20112722
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sildenafil in Liquor and Health Wine Using Surface Enhanced Raman Spectroscopy

Abstract: The illegal adulteration of sildenafil in herbal food supplements and alcoholic drinks immensely threatens human health due to its harmful side-effects. Therefore, it is important to accurately detect and identify the presence of sildenafil in alcoholic drinks. In this study, Opto Trace Raman 202 (OTR 202) was used as surface enhanced Raman spectroscopy (SERS) active colloids to detect sildenafil. The results demonstrated that the Raman enhancement factor (EF) of OTR 202 colloids reached 1.84 × 107 and the lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…It is difficult to detect sildenafil using ordinary methods, and its presence in baijiu can result in severe health effects. Xiao and He (2019) used Opto Trace Raman 202 (OTR 202) as a surface-enhanced Raman spectroscopy (SERS) active colloid to detect sildenafil, and the results showed that the Raman enhancement factor (EF) of the OTR 202 colloid reached 1.84 × 10 7 . Thus, the limit of detection (LOD) for sildenafil in health baijiu and baijiu was found to be as low as 0.1 mg/L.…”
Section: Methods For the Detection Of Flavor Substances In Baijiumentioning
confidence: 99%
“…It is difficult to detect sildenafil using ordinary methods, and its presence in baijiu can result in severe health effects. Xiao and He (2019) used Opto Trace Raman 202 (OTR 202) as a surface-enhanced Raman spectroscopy (SERS) active colloid to detect sildenafil, and the results showed that the Raman enhancement factor (EF) of the OTR 202 colloid reached 1.84 × 10 7 . Thus, the limit of detection (LOD) for sildenafil in health baijiu and baijiu was found to be as low as 0.1 mg/L.…”
Section: Methods For the Detection Of Flavor Substances In Baijiumentioning
confidence: 99%
“…Some determination methods have high sensitivity, such as GC/MS, LC/MS, nuclear magnetic resonance (NMR) spectroscopy, etc., but their developments are limited by the complex and time-consuming sample pretreatment process, large instrument, and high cost, which are not suitable for on-site detection. Xiao et al [ 158 ] used OTR 202 as a SERS-active substrate for the detection of sildenafil. The Raman enhancement factor (EF) of OTR 202 colloid was 1.84 × 10 7 , and the LOD of sildenafil in health wine and liquor was as low as 0.1 mg/L.…”
Section: Application Of Sers In the Detection Of Alcoholic Beveragesmentioning
confidence: 99%
“…The results demonstrated that the Raman enhancement factor of OTR 202 colloids reached 1.84 × 107 and the limits of detection (LODs) at 0.1 mg L −1 . Moreover, the SERS peaks of 645, 814, 1235, 1401, 1530 and 1584 cm −1 could be identified as characteristic sildenafil’s peaks [ 142 ]. Two other spectroscopic methods, a near-infrared (NIRS) [ 143 ], and a Raman method [ 144 ] were suggested as rapid screening techniques for Viagra ® tablets.…”
Section: Analytical Strategies For the Determination Of Sildenafil In Pharmaceutical And Biological Matricesmentioning
confidence: 99%
“…In the last decade, various bioanalytical methods have been reported in the literature dedicated to the analysis of sildenafil [ 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 ]. An overview is presented in Table 5 [ 30 , 123 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , ...…”
Section: Analytical Strategies For the Determination Of Sildenafil In Pharmaceutical And Biological Matricesmentioning
confidence: 99%